Effect Of Laminating Press’s Opening-Stacking Position On Adhesive Thickness In Coverlay/Adhesive/Flexible-Printed-Circuit Sheet - Lau, Kok Tee; Kok, Hoi Ern; Ab Maulod, Hairul Effendy; Abdul Latiff, Nurizzatul Zahirah; Abdul Aziz, Aida Nazifa; Rosli, Nur Hazirah (MMU Press, 2019)
This study is to investigate the dependence of coverlay’s adhesive thickness on the laminating press’s opening-stacking position. Coverlays using acrylic- and epoxy-based adhesives were laminated onto similar size copper clad laminate (CCL) at 140 bars and 195°C for 150 min. Adhesive thickness measurements show opening-stacking positions near to the bottom of laminating press machine produced more consistent adhesive thickness as compared to the top positions.